Finite Element Modelling of FRCM-Confined RC Columns Exposed to Fire - Talo, Reem (2023)
A Master of Science thesis in Civil Engineering by Reem Talo entitled, “Finite Element Modelling of FRCM-Confined RC Columns Exposed to Fire”, submitted in June 2023. Thesis advisor is Dr. Farid Abed and thesis co-advisor is Dr. Ahmed El Refai. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).